2007
DOI: 10.1007/s10439-007-9257-2
|View full text |Cite
|
Sign up to set email alerts
|

DPIV Prediction of Flow Induced Platelet Activation—Comparison to Numerical Predictions

Abstract: Abstract-Flow induced platelet activation (PA) can lead to platelet aggregation, deposition onto the blood vessel wall, and thrombus formation. PA was thoroughly studied under unidirectional flow conditions. However, in regions of complex flow, where the platelet is exposed to varying levels of shear stress for varying durations, the relationship between flow and PA is not well understood. Numerical models were developed for studying flow induced PA resulting from stress histories along Lagrangian trajectories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 17 publications
2
30
0
1
Order By: Relevance
“…These observations are physically similar to the separation of the boundary-layer downstream of stenoses, where Raz et al [30] showed the direct relationship between platelet recirculation time and both platelet activation and acetylated thrombin generation. Furthermore, Rayz et al [31] observed thrombus deposition in certain regions of patient-specific intracranial geometries with an increase in residence time and low WSS.…”
Section: Introductionsupporting
confidence: 75%
“…These observations are physically similar to the separation of the boundary-layer downstream of stenoses, where Raz et al [30] showed the direct relationship between platelet recirculation time and both platelet activation and acetylated thrombin generation. Furthermore, Rayz et al [31] observed thrombus deposition in certain regions of patient-specific intracranial geometries with an increase in residence time and low WSS.…”
Section: Introductionsupporting
confidence: 75%
“…The PAS assay was successfully applied for measuring the procoagulant activity of devices, both in vitro and in an animal model, [23][24][25] and under various shear stress-exposure time combinations in flow loops and stenosis models. 22,26 PAS values were normalized against the average activity of fully activated platelets measured for each experiment, obtained by sonication (10 W for 10 seconds, Branson Sonifier 150 with microprobe, Branson, MO). PAS values are expressed as a fraction of maximal prothrombinase activity.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…One study 42 These results suggest that in this region cells are exposed for hundreds of ms to shear stresses sustainedly larger than the normal physiological range (between 0.5 Pa and 1 Pa). The shear stresses we measured for cells travelling in the lateral orifice jet, farther from the leaflet tip, fall within the normal physiological range.…”
Section: Lagrangian Trackingmentioning
confidence: 94%